Positive electrode material with cationic disordered rock salt structure as well as preparation method and application of positive electrode material

The preparation of monodispersed cationic disordered rock salt structure LTMO cathode material was solved by the molten salt method, which solved the problem of poor cycling performance of existing materials at high voltages, and achieved higher discharge specific capacity and better cycling performance.

CN119822413APending Publication Date: 2025-04-15CHINA UNIV OF GEOSCIENCES (WUHAN)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510028112.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing cationic disordered rock salt structure positive electrode materials have poor cycling performance, fast voltage attenuation and severe capacity attenuation at high voltages, which limits their commercial applications.

Method used

The monodispersed cationic disordered rock salt structure LTMO cathode material was prepared by molten salt method. By adjusting the molar ratio and heat treatment conditions of LiOH, Mn2O3, TiO2 and Li2SO4·H2O, materials with more stable lattice oxygen were prepared.

Benefits of technology

The material exhibits better cycling stability at high voltages, has high discharge specific capacity, and has excellent cycling performance, which overcomes the voltage attenuation and capacity attenuation problems of traditional materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119822413A_ABST
    Figure CN119822413A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium batteries, and particularly discloses a monodisperse cation disordered rock salt structure positive electrode material as well as a preparation method and application thereof. The positive electrode material is a monodisperse cation disordered rock salt structure positive electrode material prepared by using lithium sulfate as a flux through a molten salt method, the surface of the positive electrode material has more stable lattice oxygen than traditional LTMO, and the lattice oxygen can effectively inhibit the irreversible oxygen redox effect of the material in the charging and discharging process. Meanwhile, due to the existence of lattice oxygen (M-O), charge transfer can be promoted, and the increase trend of charge transfer resistance of the electrode is relieved to a certain extent, so that the electrochemical performance of the material is improved. Besides, in the preparation process, no strong acid and alkali agents are introduced, complex reaction conditions are not needed, the whole process is simple, convenient and safe, and secondary pollution is small.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium-ion batteries, and in particular relates to a positive electrode material with a disordered cationic rock salt structure, and a preparation method and application thereof. Background Art

[0002] The performance of current lithium-ion batteries (LIBs) is largely limited by the available energy density in commercial cathode materials due to the large energy gap between cathode and anode materials. Recently, a variety of cation-disordered lithium-excess rock-salt structured materials have been reported as attractive LIB cathode materials. Compared with conventional cathodes such as LMO, LFP, LCO, NMC, Li- and Mn-rich (LMR) NMC, and spinel lithium nickel manganese oxide (LiNi 0.5 Mn 1.5 Compared with cation-disordered rock salt structure cathode materials (O4, LNMO), cation-disordered rock salt structure cathode materials have higher capacity. Although their average discharge voltage tends to be lower, the total energy density exceeds that of most cathodes. In addition, some cation-disordered rock salt structure cathode materials can provide more than 300 mAh g -1 and 1000Wh·kg -1 The reversible capacity and energy density of the transition metal have attracted extensive research. Therefore, cationic disordered rock salt cathode materials have become one of the choices for commercial cathode materials for next-generation lithium-ion batteries. However, the capacity contributed by the stable redox reaction of transition metals is limited. - The redox reaction provides a higher specific capacity, but this will also cause problems for the positive electrode materials. For example, compared with the current commercial positive electrode materials, this type of positive electrode material still has a series of problems such as poor cycle performance (i.e., fast capacity decay), rapid voltage decay, and fast high-rate cycle decay, which adds obstacles to its commercial application. Studies have shown that the higher the battery charging cut-off voltage, the lower the power conversion efficiency and the more serious the electrode activity decay.

[0003] The main solution to the above problems in the prior art is to use Li 1.2 Mn 0.6 Nb 0.2 O2 materials were used to introduce F and synthesize a series of chemical formulas for Li 1.2 Mn 0.6+0.5x Nb 0.2-0.5x O 2-x F xThe results show that the introduction of a certain proportion of F reduces the irreversible O redox activity and increases the contribution of cation redox to capacity, making the redox activity of transition metals and O better combined in the cation disordered salt rock structure cathode material, showing good electrochemical stability in long-term cycles. 1.2 Ti 0.4 Mn 0.4 O2 was coated with an Al2O3 layer. Through research, it was found that the Al2O3 coating layer inhibited the release of O and the adverse reaction of the electrode material interface. However, due to the interaction between Al2O3 and Li 1.2 Ti 0.4 Mn 0.4 The crystal structure of O2 varies greatly, the crystal matching is poor, and it is an inactive oxide. After coating, the activation of the material increases, and the capacity and rate performance of the battery decrease significantly.

[0004] Therefore, providing a simple and effective method to prepare cationic disordered rock salt structure positive electrode materials with high discharge specific capacity and stable cycle performance is a technical problem that scientific researchers urgently need to solve. Summary of the invention

[0005] The purpose of the present invention is to provide a cationic disordered rock salt structure positive electrode material and its preparation method and application in view of the shortcomings of the prior art. The microscopic state of the positive electrode material is monodisperse particles, and has better cycle stability under high voltage.

[0006] To achieve the above object, the present invention adopts the following technical solution:

[0007] The first object of the present invention is to provide a method for preparing a monodisperse cationic disordered rock salt structure positive electrode material, comprising the following steps:

[0008] S1. LiOH, Mn2O3, TiO2 and Li2SO4·H2O are weighed according to a certain stoichiometric amount, and after the first ball milling, the first heat treatment is performed and then naturally cooled to obtain a precursor powder.

[0009] S2, grinding the precursor powder obtained in step S1 in an agate mortar, washing with deionized water to separate the water-soluble lithium salt, collecting the M-LTMO powder by centrifugation, and vacuum drying, wherein the molar ratio of the amount of Li2SO4·H2O to the monodisperse cationic disordered rock salt structure LTMO is in the range of 1:(4-10);

[0010] S3. The dried M-LTMO powder obtained in step S2 is subjected to a second heat treatment and a second ball milling to obtain a monodisperse cationic disordered rock salt structure LTMO positive electrode material.

[0011] Furthermore, the molar ratio of LiOH, Mn2O3, TiO2 and Li2SO4·H2O is 6:1:2:1.

[0012] Furthermore, in step S1, the process of the first heat treatment is: heating to 850-1000°C at a heating rate of 3-5°C / min and keeping the temperature for 8-15h, and then cooling to 300°C at a cooling rate of 1-2°C / min.

[0013] Furthermore, in step S3, the first heat treatment process is: in an argon atmosphere, at 600-750° C. for 6-10 hours.

[0014] Furthermore, the grinding process of the first ball milling and the second ball milling is: the powder is ground in a planetary ball mill at a rotation speed of 200-400 r / min for 2-8 hours, and the mass ratio of the ball mill to the powder is 1:(2-2.5).

[0015] The second object of the present invention is to provide a cationic disordered rock salt structure positive electrode material prepared by the above preparation method.

[0016] Furthermore, the crystal structure of the cationic disordered rock salt structure positive electrode material belongs to the Fm-3m (225) space group.

[0017] Furthermore, the X-ray diffraction spectrum of the cationic disordered rock salt structure positive electrode material has a corresponding Diffraction peaks of crystal planes.

[0018] The third object of the present invention is to provide an electrode comprising the above-mentioned cationic disordered rock salt structure positive electrode material.

[0019] The fourth object of the present invention is to provide a lithium secondary battery, which comprises: a cathode, an anode, and a diaphragm, wherein the diaphragm is located between the cathode and the anode; wherein the anode comprises the above-mentioned cationic disordered rock salt structure positive electrode material.

[0020] It should be noted that in the present invention, the expressions "monodisperse cationic disordered rock salt structure LTMO" and "monodisperse cationic disordered rock salt structure LTMO positive electrode material" have the same meaning.

[0021] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:

[0022] (1) The present invention provides a monodisperse cationic disordered rock salt structure positive electrode material, which uses a monodisperse cationic disordered rock salt structure LTMO prepared by a molten salt method, and has more stable lattice oxygen (MO, M = transition metal) on its surface than traditional LTMO. It is the role of these lattice oxygens that can effectively inhibit the irreversible oxygen redox reaction of the material during the charge and discharge process. At the same time, the presence of lattice oxygen (MO) can promote charge transfer and, to a certain extent, slow down the increasing trend of the charge transfer resistance of the electrode. This makes the monodisperse cationic disordered LTMO (denoted as M-LTMO) prepared by the molten salt method have excellent electrochemical properties, and the material has better cycle stability under high voltage.

[0023] (2) The battery assembled using the monodisperse cationic disordered rock salt structure positive electrode material provided by the present invention not only has a high discharge specific capacity, but also has good cycle performance, overcoming the problems of poor cycle performance, severe voltage hysteresis, structural degradation, and other poor performance of the cationic disordered rock salt structure positive electrode material in the prior art.

[0024] (3) The preparation process of the present invention is simple and easy to control, does not involve the introduction of strong acid or alkaline reagents, and does not require complicated reaction conditions. Therefore, the entire etching process is simple and safe, with little secondary pollution, can be mass-produced, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is a characteristic comparison diagram of the positive electrode material M-LTMO prepared in Example 1 and the positive electrode material LTMO prepared in Comparative Example 1, in which (a) is LTMO; (b) is a particle size distribution diagram of LTMO and M-LTMO, and (c) is a SEM image of M-LTMO;

[0026] Figure 2 XRD spectra of the cathode material M-LTMO prepared in Example 1 before and after modification and the refined result diagram, in which (a) is LTMO and (b) is M-LTMO;

[0027] Figure 3 HRTEM images of (a) LTMO and (f) M-LTMO prepared in Example 1 of the present invention and the corresponding HRTEM magnified images and selected area electron diffraction; (be) EDS element distribution diagram of LTMO; (gj) EDS element distribution diagram of M-LTMO.

[0028] Figure 4 The XPS spectra of O1s of the positive electrode material in the original state, charged to 4.8V and discharged to 1.5V, and discharged to 1.5V after 30 cycles. (a) is LTMO and (b) is M-LTMO.

[0029] Figure 5The XPS spectra of Mn 2p of the positive electrode material in the original state, charged to 4.8V and discharged to 1.5V, and discharged to 1.5V after 30 cycles, in which (a) is LTMO and (b) is M-LTMO;

[0030] Figure 6 For positive electrode materials, the -1 CV curves below, (a) is LTMO, (b) is M-LTMO;

[0031] Figure 7 EELS spectra of the K-edge of O of LTMO and M-LTMO in different charge states in Example 1 of the present invention;

[0032] Figure 8 The first 50 charge and discharge curves of LTMO and M-LTMO prepared in Example 1 of the present invention (plotted every 5 cycles), where a is LTMO and b is M-LTMO;

[0033] Fig. 9 The LTMO and M-LTMO electrodes prepared in Example 1 of the present invention were heated to 20 mAg. -1 Comparison of cycling performance under different current densities. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical scheme and advantages of the present invention clearer, the specific embodiments of the present invention are further described in detail below in conjunction with specific examples and drawings. If no specific test method, instrument or condition is specified in the examples, it is carried out according to the technology or condition described in the literature in this field or according to the product instructions. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be obtained commercially.

[0035] Example 1

[0036] This embodiment provides a monodisperse cation disordered rock salt structure positive electrode material (Li 1.2 Mn 0.4 Ti 0.4 O2) preparation method, the specific method is as follows:

[0037] Step 1, LiOH, Mn2O3, TiO2 and Li2SO4·H2O are weighed according to a certain stoichiometric amount, the precursor is ball-milled for 4 hours, heated to 950°C at a heating rate of 3°C / min and kept warm for 12 hours, then cooled to 300°C at a cooling rate of 2°C / min, and then cooled naturally; wherein: the molar ratio of the flux Li2SO4·H2O to the monodisperse cationic disordered rock salt structure LTMO is 1:6.

[0038] Step 2: The obtained powder was recovered from the crucible, ground in an agate mortar, and washed with deionized water to separate the material from the water-soluble lithium salt. The M-LTMO powder was collected by centrifugation and dried in a vacuum oven at 60°C.

[0039] Step 3, heat treatment was then performed at 750°C in an Ar atmosphere for 10 h. Then, ball milling was performed at 400 rpm for 4 h. Thus, a monodisperse cationic disordered rock salt structure positive electrode material was obtained, which was recorded as M-LTMO.

[0040] Example 2

[0041] This embodiment provides a monodisperse cation disordered rock salt structure positive electrode material (Li 1.2 Mn 0.4 Ti 0.4 O2) preparation method, the specific method is as follows:

[0042] Step 1, LiOH, Mn2O3, TiO2 and Li2SO4·H2O are weighed according to a certain stoichiometric amount, the precursor is ball-milled for 4 hours, heated to 950°C at a heating rate of 3°C / min and kept warm for 12 hours, then cooled to 300°C at a cooling rate of 2°C / min, and then cooled naturally; wherein: the molar ratio of the flux Li2SO4·H2O to the monodisperse cationic disordered rock salt structure LTMO is 1:4.

[0043] Step 2: The obtained powder was recovered from the crucible, ground in an agate mortar, and washed with deionized water to separate the material from the water-soluble lithium salt. The M-LTMO powder was collected by centrifugation and dried in a vacuum oven at 60°C.

[0044] Step 3, heat treatment was then performed at 750° C. in an Ar atmosphere for 10 h, and then ball milling was performed at 400 rpm for 4 h to obtain the product.

[0045] Example 3

[0046] This embodiment provides a monodisperse cation disordered rock salt structure positive electrode material (Li 1.2 Mn 0.4 Ti 0.4 O2) preparation method, the specific method is as follows:

[0047] Step 1, LiOH, Mn2O3, TiO2 and Li2SO4·H2O are weighed according to a certain stoichiometric amount, the precursor is ball-milled for 4 hours, heated to 950°C at a heating rate of 3°C / min and kept warm for 12 hours, then cooled to 300°C at a cooling rate of 2°C / min, and then cooled naturally; wherein: the molar ratio of the flux Li2SO4·H2O to the monodisperse cationic disordered rock salt structure LTMO is 1:8.

[0048] Step 2: The obtained powder was recovered from the crucible, ground in an agate mortar, and washed with deionized water to separate the material from the water-soluble lithium salt. The M-LTMO powder was collected by centrifugation and dried in a vacuum oven at 60°C.

[0049] Step 3, heat treatment is then performed at 750°C in an Ar atmosphere for 10 hours, followed by ball milling at 400 rpm for 4 hours, to obtain a high voltage, long cycle monodisperse cation disordered LTMO cathode material.

[0050] Example 4

[0051] This embodiment provides a monodisperse cation disordered rock salt structure positive electrode material (Li 1.2 Mn 0.4 Ti 0.4 O2) preparation method, the specific method is as follows:

[0052] Step 1, Li2CO3, Mn2O3, TiO2 and Li2SO4·H2O are weighed according to a certain stoichiometric amount, the precursor is ball-milled for 4 hours, heated to 950°C at a heating rate of 3°C / min and kept warm for 12 hours, then cooled to 300°C at a cooling rate of 2°C / min, and then cooled naturally; wherein: the molar ratio of the flux Li2SO4·H2O to the monodisperse cationic disordered rock salt structure LTMO is 1:6.

[0053] Step 2: The obtained powder was recovered from the crucible, ground in an agate mortar, and washed with deionized water to separate the material from the water-soluble lithium salt. The M-LTMO powder was collected by centrifugation and dried in a vacuum oven at 60°C.

[0054] Step 3, heat treatment at 750°C in an Ar atmosphere for 10 hours, and then ball milling at 400 rpm for 4 hours to obtain a cation disordered LTMO positive electrode material.

[0055] Comparative Example 1

[0056] This embodiment provides a positive electrode material (Li 1.2 Mn 0.4 Ti 0.4 O2) preparation method.

[0057] The method is basically the same as Example 1, except that lithium chloride is used as the flux.

[0058] Comparative Example 2

[0059] This embodiment provides a positive electrode material (Li 1.2 Mn 0.4 Ti 0.4 O2) preparation method.

[0060] It is basically the same as Example 1, except that lithium nitrate is used as the flux.

[0061] Comparative Example 3

[0062] This embodiment provides a positive electrode material (Li 1.2 Mn 0.4 Ti 0.4 O2) preparation method.

[0063] It is basically the same as Example 1, except that the flux is lithium acetate, and the molar ratio of LiC2H3O2 and monodisperse cationic disordered LTMO is 1:6.

[0064] Comparative Example 4

[0065] This embodiment provides a positive electrode material (Li 1.2 Mn 0.4 Ti 0.4 O2) preparation method.

[0066] It is basically the same as Example 1, except that lithium phosphate is used as the flux.

[0067] Comparative Example 5

[0068] This embodiment provides a method for preparing a positive electrode material with a disordered cationic rock salt structure, and the specific method is as follows:

[0069] Step 1, weigh LiOH, Mn2O3 and TiO2 respectively according to a certain stoichiometric amount, ball mill the precursor for 4 hours, grind the mixture at a speed of 300r / min for 6 hours, wherein the mass ratio of the ball mill to the powder is 1:2.5, to obtain a uniformly mixed powder raw material precursor.

[0070] Step 2: Press the precursor compound into hard discs with a size of 0.5 g / tablet using a tablet press, then put the hard discs into a tube furnace, and anneal them at 900° C. in an argon atmosphere for 12 hours to obtain dark blue-gray hard discs after annealing.

[0071] Step 3, the dark blue-gray hard discs are preliminarily crushed, packaged into a ball mill jar under an argon atmosphere, and then placed in a ball mill for grinding the mixture at a speed of 200 r / min and 400 r / min for 2 hours and 4 hours, respectively, wherein the mass ratio of the ball mill to the powder is 1:2, to obtain a powder raw material after particle refinement, with an average particle size of about 100 nm to about 180 nm, recorded as LTMO-5.

[0072] Comparative Example 6

[0073] This embodiment provides a method for preparing a positive electrode material with a disordered cationic rock salt structure, and the specific method is as follows:

[0074] Step 1, weigh Li2CO3, Mn2O3 and TiO2 respectively according to a certain chemical amount, weigh the precursor and ball mill it for 4 hours, grind the mixture at a speed of 300r / min for 6 hours, wherein the mass ratio of the ball mill to the powder is 1:2.5, to obtain a uniformly mixed powder raw material precursor.

[0075] Step 2: Press the precursor compound into hard discs with a size of 0.5 g / tablet using a tablet press, then put the hard discs into a tube furnace, and anneal them at 900° C. in an argon atmosphere for 12 hours to obtain dark blue-gray hard discs after annealing.

[0076] Step 3, the dark blue-gray hard discs are preliminarily crushed, packaged into a ball mill jar under an argon atmosphere, and then placed in a ball mill for grinding the mixture at a speed of 200 r / min and 400 r / min for 2 hours and 4 hours, respectively, wherein the mass ratio of the ball mill to the powder is 1:2, to obtain a powder raw material after particle refinement, with an average particle size of about 100 nm to about 180 nm, recorded as LTMO-6.

[0077] Performance characterization:

[0078] The cationic disordered rock salt structure positive electrode materials prepared in Examples 1-3 have similar microscopic morphology and structure, which are described using Example 1 and Comparative Example 1 as examples.

[0079] refer to Figure 1 , (a) and (c) show the SEM images of LTMO and M-LTMO respectively. Figure (a) shows that after high-temperature annealing, the particles of LTMO present irregular shapes and are accompanied by small particle agglomeration. (c) M-LTMO prepared by the molten salt method, it can be seen that the particle surface is smooth, not rough, the particles are evenly distributed, the size is moderate, and there is no agglomeration. As shown in (b), it can be seen that the particle size distribution of LTMO particles is relatively wide, with an average particle size of 30μm, a large size span, and an uneven particle size distribution. However, the monodisperse M-LTMO prepared by the molten salt method has a narrow particle size distribution, an average particle diameter of ~10μm, a uniform distribution, and a single particle.

[0080] refer to Figure 2 , showing that the Rietveld XRD refinement results of LTMO and M-LTMO are both cationic disordered structures with Fm-3m (225) space group. It can be seen that even if the process is changed, the synthesized materials still belong to the cationic disordered rock salt structure without the presence of other impurity phases.

[0081] refer to Figure 3, (a) and (f) show the high-resolution electron microscopy images and corresponding selected area electron diffraction patterns of the two comparative materials. The lattice spacings of LTMO and M-LTMO are 0.204nm and 0.206nm, respectively. The slight difference between the two may come from measurement errors, but they are consistent with the interplanar spacing of the (002) plane of the structure, proving that both materials in this study belong to cationic disordered rock salt structures. TEM-EDS results (be) and (gi) show that elements such as Mn, Ti, and O are uniformly distributed in the material.

[0082] refer to Figure 4 (a) and (b) show the O1s spectra of the two samples in the original state, charged to 4.8V and discharged to 1.5V, and discharged to 1.5V after 30 cycles. It can be seen that the O1s spectra of the two samples show considerable differences. For M-LTMO, the O 1s spectrum in Figure (b) shows that the relative intensity changes of these peaks are not obvious during the 1st to 30th cycles. This result shows that the monodisperse M-LTMO prepared using the molten salt method successfully stabilizes the lattice oxygen in the cation-disordered material. This preparation method can significantly reduce the number of intrinsic oxygen vacancies and unstable O 2p holes in Li-Mn-rich oxides, which helps to achieve reversible redox reactions of oxygen and inhibit the loss of lattice oxygen.

[0083] refer to Figure 5 (a) and (b) show the XPS test results of LTMO and M-LTMO in their original state, constant current charging to 4.8 V, constant current discharge to 1.5 V, and after 30 cycles of discharge to 1.5 V. The peaks at 641.2 eV and 652.3 eV in the Mn 2pXPS spectra of LTMO and M-LTMO samples are Mn 3+ 2p 3 / 2 and 2p 1 / 2 In addition, the peak at 642.8 eV corresponds to Mn 4+ 2p 3 / 2 and 2p 1 / 2 characteristic peaks.

[0084] In order to better illustrate the electrochemical performance of the lithium-ion battery positive electrode material of the present invention, the applicant has also conducted the following research:

[0085] Preparation of electrode samples:

[0086] The lithium battery positive electrode material sample powder and Ketjen black of the present invention were weighed at a weight ratio of 7:2, respectively, and encapsulated into a ball mill jar under an argon atmosphere, and then placed in a ball mill at a speed of 200r / min and 400r / min, respectively, for high-energy grinding for 2 hours and 4 hours. Then, polytetrafluoroethylene (PTFE) was weighed as a binder at a weight ratio of 7:2:1 and added to the mixture of the lithium battery positive electrode material sample powder and Ketjen black. The three components were manually mixed in a glove box with an argon atmosphere for 30 minutes to prepare a thin film electrode sheet.

[0087] The prepared cathode film is assembled into a battery for conventional cycle testing. Using LiPF6 added to ethylene carbonate (EC) and dimethyl carbonate (DMC) solution (volume ratio of 1:1), with metallic lithium as the negative electrode, glass fiber membrane (GE Whatman) as the separator, 1.0 mol / L LiPF6 / ethylene carbonate (EC) + dimethyl carbonate (DMC) solution (EC:DMC=1:1, vol%) as the electrolyte, it is assembled into a Swagelok-type mold battery shell in an argon glove box. The assembled battery was tested with the LAND battery tester produced by Wuhan Jinnuo Electronics Co., Ltd. The cathode film load density was about 6 mgcm -2 The specific capacity was calculated based on the amount of lithium metal oxide component in the cathode film (i.e. 70% by weight) under the following test conditions: the charge and discharge voltage range was 1.5 to 4.8 V, and the current density was 20 mA g -1 Perform constant current charge and discharge test.

[0088] The positive electrode materials prepared in Examples 1-4 and Comparative Examples 1-6 were respectively used to prepare electrode plates according to the above method, and then a discharge test was performed. The test results are shown in Table 1:

[0089] Table 1. Test results

[0090]

[0091] refer to Figure 6 (a) and (b) show the CV curves of the two samples, and the results show that their overall characteristics are basically the same. It can be seen that the overlap of the CV curves of M-LTMO after 10 cycles is much better than that of LTMO, indicating that it has excellent cycle reversibility, which is also the reason why it has better cycle stability.

[0092] refer to Figure 7, comparing (a) and (b) in the figure, it can be seen that the OK edge of M-LTMO basically returns to its original state after the first cycle; after 50 cycles of constant current charge and discharge, although the relative intensity decreases, the front peak intensity is clearly visible, and the coincidence of M-LTMO is better in comparison. This shows that reversible O redox reaction occurs in the first electrochemical cycle of both materials, but the reversibility of M-LTMO is better in subsequent cycles.

[0093] refer to Figure 8 (a) and (b) show the charge and discharge curves of the two samples in the first 50 cycles (drawn every 5 cycles). It can be seen from the figure that the specific capacity of LTMO decays significantly after 50 cycles, while the specific capacity retention rate of M-LTMO is better.

[0094] refer to Fig. 9 The cycling performance comparison results of the two samples are shown. The initial discharge capacity of LTMO is 254.3 mAh g -1 After 50 cycles, the specific capacity is only 113.7 mAh g -1 The capacity retention rate is only 44.71%. The initial specific capacity of M-LTMO is close to that of LTMO, which is 245.5 mAh g -1 However, its specific capacity after 50 cycles can still reach 200.7 mAh g -1 , the capacity retention rate is as high as 81.75%, which is much higher than that of LTMO materials.

[0095] In the absence of conflict, the above embodiments and features in the embodiments may be combined with each other.

[0096] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a monodisperse cationic disordered rock salt structure positive electrode material, characterized in that: The following steps are involved: S1. LiOH, Mn2O3, TiO2 and Li2SO4·H2O are weighed according to a certain stoichiometric amount, subjected to a first ball milling, and then subjected to a first heat treatment and natural cooling to obtain a precursor powder; S2, grinding the precursor powder obtained in step S1 in an agate mortar, washing with deionized water to separate the water-soluble lithium salt, collecting the powder by centrifugation, and vacuum drying to obtain a dry M-LTMO powder, wherein the molar ratio of the amount of Li2SO4·H2O to the monodisperse cationic disordered rock salt structure LTMO is in the range of 1:(4-10); S3. After the dried M-LTMO powder obtained in step S2 is subjected to a second heat treatment, it is subjected to a second ball milling to obtain a monodisperse cationic disordered rock salt structure LTMO positive electrode material.

2. The preparation method according to claim 1, characterized in that The molar ratio of LiOH, Mn2O3, TiO2 and Li2SO4·H2O is 6:1:2:

1.

3. The preparation method according to claim 1, characterized in that: In step S1, the process of the first heat treatment is: heating to 850-1000°C at a heating rate of 3-5°C / min and keeping the temperature for 8-15h, and then cooling to 300°C at a cooling rate of 1-2°C / min.

4. The preparation method according to claim 1, characterized in that: In step S3, the first heat treatment process is: in an argon atmosphere, at 600-750° C. for 6-10 hours.

5. The preparation method according to claim 1, characterized in that: The grinding process of the first ball milling and the second ball milling is: the powder is ground in a planetary ball mill at a rotation speed of 200-400 r / min for 2-8 hours, and the mass ratio of the ball mill to the powder is 1:(2-2.5).

6. A cationic disordered rock salt structure positive electrode material prepared by the preparation method as described in any one of claims 1 to 5.

7. The cationic disordered rock salt structure positive electrode material according to claim 6, characterized in that: The crystal structure of the cationic disordered rock salt structure positive electrode material belongs to the Fm-3m (225) space group.

8. The cationic disordered rock salt structure positive electrode material according to claim 6, characterized in that: The X-ray diffraction spectrum of the cationic disordered rock salt structure positive electrode material has a range of 10 to 90 degrees corresponding to Diffraction peaks of crystal planes.

9. An electrode, characterized in that: Contains the cationic disordered rock salt structure positive electrode material as described in any one of claims 6 to 8.

10. A lithium secondary battery, characterized in that: The lithium secondary battery comprises: a cathode, an anode, and a separator, wherein the separator is located between the cathode and the anode; wherein the anode comprises the cationic disordered rock salt structure positive electrode material as described in any one of claims 6-8.